Pengaruh Citra Merek, Kualitas Produk, Harga, Serta Celebrity Endorser Terhadap Keputusan Pembelian Pada Produk Scarlet Di Yogya Mall Brebes - Sulisti Zulia Aprilianti; Yumna Nada Salsabila; Slamet Bambang Riono; Hendri Sucipto; Akbar NPD Wahana (Universitas 17 Agustus 1945 Semarang, 2023)
This research aims to explore the consequences of brand image, product quality, price, and celebrity endorsers on consumers' tendency to buy Scarlet Whitening Body Lotion products again. Survey participants included consumers who bought and used Scarlet Whitening Body Lotion products from Yogya Mall Brebes, with a total of 464 people. The research sample was taken as much as 25% of the population, namely 116 respondents, with the implementation of random selection procedures. The information collection equipment used is a questionnaire that has been tested for validity, reliability, and meets the assumptions of classical responses. The data were tested by multiple regression analysis, t test, F test, as well as coefficient of determination. The results show that brand image has a positive and significant influence on purchasing decisions. Product variables have no effect on purchasing decisions, price and celebrity endorsers have no effect on purchasing decisions. In totality, brand image, product quality, price, and celebrity endorsers have an influence on the purchase decision of Scarlet Whitening Body Lotion products.